Formazanido complexes of heavier group 13 elements aluminium, gallium, and indium. Issue 3 (14th December 2015) - Schorn, W.; Grosse-Hagenbrock, D.; Oelkers, B.; Sundermeyer, J.
Abstract : The straightforward synthesis and detailed characterization both in solution and in the solid state of novel triphenylformazanido complexes of group 13 elements Al, Ga, In is reported. Abstract : The preparation, molecular structures and physical properties of novel heavy group 13 metal formazanido complexes are described. The trimethyl derivatives MMe3 (M = Al, Ga, In) react with 1, 3, 5-triphenylformazan (Htpf) in a 1 : 1 ratio to give methane and metallacycles of the type [M(tpf)Me2 ]. While [Al(tpf)Me2 ] and [Ga(tpf)Me2 ] are mononuclear compounds with six-membered rings and coordination number 4 in solution and in the crystalline state, indium derivative [In(tpf)Me2 ] forms oligomers in non-coordinating solvents according to NMR studies, these are probably N-bridged dimers with coordination number 5 at indium. The oligomer is cleaved by addition of one equivalent of pyridine or 4-dimethylaminopyridine (DMAP). The complexes [M(tpf)Me2 ] (M = Al, Ga) and [In(tpf)Me2 (DMAP)] are characterized by XRD analyses. They are unique examples of main group metal formazane ring systems of the third and higher periods. The UV-Vis solution spectra of the neutral ligand Htpf and its metallated compounds [M(tpf)Me2 ] (M = Al, Ga, In) are discussed.